1979
DOI: 10.1093/nar/6.11.3543
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of synthetic oligodeoxyribonucleotides to ΦX174 DNA: the effect of single base pair mismatch

Abstract: Oligodeoxyribonucleotides complementary to the DNA of the wild type (wt) bacteriophage phi chi 174 have been synthesized by the phosphotriester method. The oligomers, 11, 14, and 17 bases long, are complementary to the region of the DNA which accounts for the am-3 point mutation. When hybridized to am-3 DNA, the oligonucleotides form duplexes with a single base pair mismatch. The thermal stability of the duplexes formed between wt and am-3 DNAs has been measured. The am-3 DNA:oligomer duplexes dissociate at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
292
0
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 700 publications
(296 citation statements)
references
References 25 publications
1
292
0
2
Order By: Relevance
“…Also it was found that different regions of a random piece of DNA melted at different temperatures which are dependent on base pair content (Wada et al, 1976 (Szer & Shugar, 1966) that stability of the helix was altered and this was confirmed in the mid 1970s (Engel & von Hippel, 1974Gill et al, 1974;Ehrlich et al, 1975). These findings were put on a more systematic basis by Wallace and coworkers who showed that synthetic oligonucleotides of 11, 14 and 17 bases were less stable when they contained a single base pair mismatch in the duplex (Wallace et al, 1979). The extension and application of these findings are discussed below.…”
Section: Isolation Of Genetic Materialsmentioning
confidence: 90%
“…Also it was found that different regions of a random piece of DNA melted at different temperatures which are dependent on base pair content (Wada et al, 1976 (Szer & Shugar, 1966) that stability of the helix was altered and this was confirmed in the mid 1970s (Engel & von Hippel, 1974Gill et al, 1974;Ehrlich et al, 1975). These findings were put on a more systematic basis by Wallace and coworkers who showed that synthetic oligonucleotides of 11, 14 and 17 bases were less stable when they contained a single base pair mismatch in the duplex (Wallace et al, 1979). The extension and application of these findings are discussed below.…”
Section: Isolation Of Genetic Materialsmentioning
confidence: 90%
“…This technique has been used previously in analyses of 4~X-174 bacteriophage DNA (Wallace et al, 1979), rabbit beta-globulin DNA , sickle cell betas-globulin allele (Conner et al, 1983), mutations in codon 61 of the human N-ras gene (Bos et al, 1984), and in the diagnosis of enterotoxogenic Escherichia coli (Hill et al, 1985). As in oligonucleotide fingerprinting, hybridization with short probes can detect a change in one or more bases (Wallace et al, 1979). Moreover, hybridization results are available in less than 24 h, as compared with fingerprinting, which requires a minimum of 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Colonies with inserts were initially identified by using an oligonucleotide probe spanning the entire P1 ori region targeted for mutagenesis. Using a series of seven overlapping oligonucleotide probes of 16 to 19 bases in length, clones likely to contain inserts with single-base changes were identified by using stringent hybridization conditions to detect single-base-pair mismatches (33,34). This also allowed us to determine in which short interval the putative mutation was located.…”
Section: Methodsmentioning
confidence: 99%